Evaluation of Hirschsprung’s Disease in a Pediatric Hospital in Southern Iran During 2005-2013 - Farzaneh Dehghan (Journal of Global Pharma Technology, 2018)
Background: Hirschsprung’s disease (HD) is a congenital absence of ganglion cells in the lining of the large intestine that can cause functional intestinal obstruction. Objective: The aim of this study was to investigate the incidence of Hirschsprung's disease in patients referring to a pediatric hospital in south of Iran over a period of 9 years. Methods: This retrospective research was carried out on all neonates, infants and children who referred to the largest pediatric Hospital of Hormozgan in Bandar Abbas, Southern of Iran due to suspected signs and symptoms of hirschsprung’s disease during the 9 years from March, 2005 to March, 2013.Demographic data and clinical symptoms of these patients were extracted from medical records available in hospital archives by a checklist. Results: Among the 85177 hospitalized patients in koodakan hospital of Bandar Abbas, a total of 425 cases had Hirschsprung’s disease (HD) with an overall male-to-female incidence ratio of 1.72. An overall increasing trend was observed in studied time. Chronic constipation (92.2%) and abdominal distension (91.1%) were the most common complaints. There were 21 deaths (4.9%) in cases with HD but none of the deaths in this population were attributable to HD. Conclusions: Based on the result the incidence of hirschsprung’s disease was elevated in recent years. However, more studies in several provinces are required to determine the exact value of incidence and further associations.Keywords: Hirschsprung’s disease, neonates, infants, children